Between blue and light - Campbell, Jennifer (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2018)
My novella follows a narrator observing her life, as she struggles with what it is to live in a world that she finds simultaneously frightening and beautiful. The story touches on the limitations of human connection and with loss in various forms. Set in both Cape Town and small town South Africa, the story explores the inner life of a woman detached and adrift.
Keywords: South African fiction (English) -- 21st century; Short stories, South African (English) -- 21st century